I solved one question in a book of analysis, and although I used an informal method to check it, I'd like to know more about what should be done. The question was the following:

  1. $A\subset X$ and $ B \subset X$;

  2. If $A\subset Y$ and $ B\subset Y$, then $X\subset Y$.

Prove that $X=A\cup B$.

Looking at the second line, we have an implication. If $Q$, then $P$. And it's truth table is the following:

$$\begin{matrix} {P}&{Q}&{}&{P\rightarrow Q}\\ {0}&{0}&{}&{1}\\ {0}&{1}&{}&{1}\\ {1}&{0}&{}&{0}\\ {1}&{1}&{}&{1} \end{matrix}$$

Then $Q\equiv A\subset Y, B\subset Y$ and $P\equiv X\subset Y$, to answer it, what line should I take from that truth table? I did by thinking that $P=1$ and $Q=1$, but there are other choices too. Is it possible to obtain the same answer with any choices of $P$ and $Q$? I've been thinking in the other ways but assuming that $P=1=Q$ seems more natural. I guess that it should be valid for every row, but I'm not sure.

  • $\begingroup$ You should prove (i) $A \cup B \subset X$ and (ii) $X \subset A \cup B$. You can prove (i) from the first statement. To prove (ii), use the second statement with $Y=A \cup B$. $\endgroup$ – Aravind Nov 23 '14 at 10:11
  • 1
    $\begingroup$ It's possible that this helps. $\endgroup$ – Git Gud Nov 23 '14 at 11:18
  • $\begingroup$ @GitGud Good! Thanks! $\endgroup$ – Billy Rubina Nov 23 '14 at 12:45

If I understand you correctly, you want to know the following:

I want to prove

$$(A\subset X \land B \subset X) \land ((A\subset Y \land B\subset Y) \rightarrow X\subset Y)\implies X=A\cup B $$

since the proposition $P \implies Q$ is formally true in the cases

$$\begin{matrix} {P}&{Q}&{}&{P\implies Q}\\ {0}&{0}&{}&{1}\\ {0}&{1}&{}&{1}\\ {1}&{1}&{}&{1} \end{matrix}$$

If I take $$P=(A\subset X \land B \subset X) \land ((A\subset Y \land B\subset Y) \rightarrow X\subset Y)$$ $$Q=(X=A\cup B)$$

Can I use any of the cases above?

The answer is no, here is a counter-example:

$A = \{1,2\}$, $B=\{3,4\}$, $X =\{1,2,3,4,5\}$ and $Y=\{2,3,4\}$

we have $A \subset X$, $B \subset X$, $A \not \subset Y$, $B \subset Y$, $X \not \subset Y$ and $X \neq A \cup B$

In this case both $A\subset X \land B \subset X$ and $(A\subset Y \land B\subset Y) \rightarrow X\subset Y$ would be true, so we should be able to prove the implication since we are in one of the cases above, but it doesn't work.

Here is how I explain it:

The proposition $P \implies Q$ is $\textbf{formally}$ true in all the cases above, but when we are trying to prove something we don't interpret it this way, it's more like a "construction", you have to show that $Q$ "depends on" $P$, and this case is only the last one in the table. Think of it as sets, you want to show that $Q \subset P$, it's always true if $Q = \emptyset$, but this one doesn't count.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.